2018
DOI: 10.1371/journal.pone.0205082
|View full text |Cite
|
Sign up to set email alerts
|

Commercialization of obstetric and neonatal care in the Democratic Republic of the Congo: A study of the variability in user fees in Lubumbashi, 2014

Abstract: ObjectiveIn the Democratic Republic of the Congo, insufficient state financing of the health system produced weak progress toward targets of Millennium Development Goals 4 and 5. In Lubumbashi, almost all women pay out-of-pocket for obstetric and neonatal care. As no standard pricing system has been implemented, there is great variation in payments related to childbirth between health facilities and even within the same facility. This work investigates the determinants of this variation.MethodsWe conducted a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 47 publications
3
16
0
Order By: Relevance
“…This is higher than the overall incidence of catastrophic expenses due to health care reported in 2014 in DRC by the World Bank, which was 10.8% [15]. In an earlier study [16], we showed that, given that the transportation network in Lubumbashi is easily accessible and affordable, the contribution of the price of transport to the total payment at the time of delivery remains low (3.2–8.2%). Thus, even without taking transport into account, the incidence of CE in Lubumbashi is higher than in urban settings in various sub-Saharan African countries [2831].…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…This is higher than the overall incidence of catastrophic expenses due to health care reported in 2014 in DRC by the World Bank, which was 10.8% [15]. In an earlier study [16], we showed that, given that the transportation network in Lubumbashi is easily accessible and affordable, the contribution of the price of transport to the total payment at the time of delivery remains low (3.2–8.2%). Thus, even without taking transport into account, the incidence of CE in Lubumbashi is higher than in urban settings in various sub-Saharan African countries [2831].…”
Section: Discussionmentioning
confidence: 60%
“…At the national level in DRC, the incidence of CE linked to general care has been reported as 10.8% [15]. In 2014, in Lubumbashi, we showed that expenses tied to obstetric care were higher when compared to other cities in Africa [16], but information on the incidence of CE, its determinants and health and socioeconomic consequences among women who deliver with skilled attendance, is lacking. The rate of skilled birth attendance is high (94.5%) despite the extent of poverty in the city [17]; we wanted to discover the strategies used by households to meet these fees despite their impoverishing nature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Figures 3 and 4 compare whether out of pocket health expenditures for normal delivery, C-section, eclampsia, and maternal hemorrhage was higher than 10% of the average gross national income per capita for different countries in sub-Saharan Africa. Out of pocket cost for normal delivery services was catastrophic for only one study from DR Congo [ 47 ], however, costs were catastrophic in eight studies out of the twelve [ 18 , 19 , 27 , 30 , 35 , 44 , 47 , 54 ] that reported delivery by the C-section. Out of pocket payments were also catastrophic in three out of six studies on the management of eclampsia [ 21 , 47 , 54 ], one out of four studies about abortion services [ 31 ], one out of three studies on the management of low birth weight babies [ 59 ] and four out of five studies on the management of hemorrhage [ 21 , 44 , 47 , 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…In fact, in the DRC, there is no nancial protection mechanism for the poorest individuals, and the few health insurance plans that exist are available only to certain public or private professional companies: Prepaid systems through voluntary health insurance plans cover only a tiny fraction of the population, i.e., 7% [5]. This constitutes a major challenge for the health system in general.In terms of obstetric and neonatal care in particular, several studies across the country have found that the cost of providing this care is expensive for households at the time of delivery and results in catastrophic costs [6][7][8][9][10]. Nevertheless, 81.5% of women give birth in a hospital environment in the presence of quali ed personnel, with a high fertility index, at the rate of 6.6 children per woman [11,12].…”
Section: Introductionmentioning
confidence: 99%